Understanding 'context' in the self-management of type 2 diabetes with comorbidities: A systematic review and realist evaluation. (August 2018) - Schmidt-Busby, Jacqueline; Wiles, Janine; Exeter, Daniel; Kenealy, Timothy
Abstract: Objective: To identify contextual factors that affect self-management of diabetes with comorbidities, and to evaluate in what way these factors affect self-management effectiveness. Methods: A systematic review of literature considered English language articles published within Medline, PsycINFO, Pubmed, CINAHL Plus, and Scopus databases that focussed on individuals' experiences of type 2 diabetes from primary intervention or observational studies. A realist evaluation approach was used to analyse themes identified within the literature. Context-mechanism-outcome theories were constructed to identify underlying contextual factors and to construct a model illustrating diabetes self-management effectiveness. Results: Of 1519 articles identified, 30 met inclusion criteria. Adherence was found to be the common mechanism that (within given contexts) determined self-management effectiveness. Limited financial resources were identified as the key context. Our model makes explicit a structural weaknesses of diabetes self-management. Conclusions: Coping with diabetes in the context of people's lives requires attention to issues that are often outside the remit of the person with diabetes, the health care team, and the health system within which self-management is located. Realist evaluations illuminate programme mechanisms and fine-tune context. They aid initial understandings of how an intervention or programme is thought to work, in order to influence and (re)design (new) programmes.